Zygomatic implant, a new beginning in Nepal: A case report and review of literature - Kumar Acharya, Surendra; Fan Choon, Yee; Kumar Ghimire, Subhash; Bimb, Kushal; Shrestha, Ashwin; Rai, Mamata (Journal of Chitwan Medical College, 2025)
Zygomatic implant (ZI) has become a promising alternative to bone grafting techniques in the rehabilitation of severely atrophied maxillae. High survival rates and easily manageable complications are key to its increased application in experienced hands. Here, we report a case of ZI placement in Nepal and review the literature. A 58-year-old female presented to the Oral and Maxillofacial Surgery Department, concerned about difficulty in chewing food. Clinical examination and 3D Cone Beam Computed Tomography evaluation deemed her a good candidate for ZIs. The classic zygoma concept was employed. Two 450 angulated, 35mm long ZIs were inserted bilaterally with two 4.2x10 implants placed in 12 and 23 regions. The procedure was carried out under local anaesthesia. Prosthetic rehabilitation was completed after six months, and 1-y follow-up revealed osseointegration of implants and prosthesis.